Pengaruh Indikasi Geografis Warisan Budaya Tradisional dalam Konteks Keju Serrano di Brazil - Rahmadini, Rizki (Global and Policy Journal of International Relations, 2015)
ABSTRACTGeographical Indication (GI) is one of Trade-Related Intellectual Property Rights (TRIPs)’ working areas. Various products registered as Geographical Indication (GI) could be found in many developed countries because since 100 years ago, their farmers have respected the relation between traditional products and place where those products were originated. However, the same thing has not done by farmers in developing countries, thus only few of their traditional products which have been registered as GI to obtain legal protection. In fact, regarding of the developing countries’ geographic potentials, if they could realize the high economic value of products produced from such geographical potentials, they will be benefitted by the existence of GI. Theoretically, TRIPs is profitable if countries could maximize the role of TRIPs. TRIPs’ role is not only considered from how the legal protection of TRIPs could avoid losses caused by criminal act, but also from how TRIPs could add the value of those products to put them in the best prices. However, practically, the role of TRIPs is still controversial in developing countries because they are still upholding their traditional cultural values, while the intellectual property rights tend to be related with the use of modern technologies. One form of such controversies could be seen in the context of Serrano Cheese in Brazil, which shows how GI affects the traditional cultural heritage of indigenous people.Keywords: Geographical Indication, TRIPs, Serrano CheeseDOI:https://doi.org/10.33005/jgp.v3i02.1936